Training of hosters to provide shared hosting in Community-Based Tourism (Citizenship in Action: Extension and Culture Magazine, 2024)
This experience report presents the extension project Mini-course Shared Hosting in Community-Based Tourism (CBT), by the Federal Institute of Santa Catarina, whose objective was the creation and execution of an online self-instructional mini-course that would offer professional training to CBT collectives, in order to prepare them to implement the hosting in their residences. The course, which lasted one month and had a workload of 20 hours, was created by an extensionist student of the Specialization in Technologies for Professional Education, under the guidance of the teacher, and had five modules that addressed introductory subjects on tourism, hosting, sustainability and operational practices to be used in the day-to-day activities at CBT. A learning platform was organized with various technological educational resources such as videos, infographics, podcasts and others. The elaboration of these materials occurred during the Specialization, mainly in its practical classes, in which students were challenged to explore educational authoring tools. We had 47 registrations and 16 participants were certified at the end. This report presents the context of the extension project, the process of creating and offering the Mini-course, the activities carried out and the evaluation of the participants. The extensionist student experienced in practice the creation of didactic resources for the digital environment and online teaching, in contact with the external community. The action provided dissemination of knowledge about CBT and encouraged improvement in the area.
Keywords: extension; professional qualification; Community Based Tourism; shared hosting